(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Genetic polymorphism of esterase isozymes was examined in different developmental stages of Gambusia affinis after staining with ?-napthyl acetate as substrate by 7.5% polyacrylamide gel electrophoresis. Samples were just after birth, seven, 14 days old fry, 21, 28, 35, 42, 49 days old male and female. Altogether three esterase bands named as Est-1, Est-2 and Est-3 were observed. Est-1 was absent in seven samples out of 13, Est-2 was absent only in just after birth, Est-3 was absent in seven different samples out of 13 samples. This result indicates that Est-1 and Est-3 were less active and Est-2 was very active at ? napthyl acetate. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10917 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 39-44, 2012